Internalisasi Etika Bisnis dalam Pembentukan Karakter Profesional Mahasiswa: (Studi Kualitatif Berbasis Pengalaman dan Praktik Sosial) - Siswohad Siswohad; Dewi Anjani; Sukma Ludda E.P.; Genies Fitri Oktavia; Adelia Candra Riska Saputri; Nur Anisatul Khoiroh (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the process of internalizing business ethics in shaping students’ professional character through academic experiences and social practices. The research focuses on how business ethics values are understood, implemented, and internalized by students in academic activities, organizational involvement, and other social interactions. This study employs a qualitative approach with a descriptive-interpretative method. Data were collected through in-depth interviews, observations, and documentation involving students actively engaged in academic and organizational activities. Data analysis was conducted through data reduction, data presentation, and thematic conclusion drawing. The findings indicate that the internalization of business ethics occurs through habituation, role modeling, social interaction, and direct experiences in facing situations that require responsibility, honesty, discipline, and professionalism. The campus environment, lecturers, student organizations, and social culture play significant roles in shaping students’ professional character. Furthermore, social practice experiences provide opportunities for moral reflection that strengthen students’ ethical awareness in decision-making. This study concludes that the internalization of business ethics is not merely theoretical but is also formed through real experiences and continuous social practices, thereby fostering professional character with integrity and responsibility.